Outcomes of patients with spinal metastases from renal cell carcinoma treated with conventionally-fractionated external beam radiation therapy. Issue 16 (April 2020) - Lee, Chia Ching; Tey, Jeremy Chee Seong; Cheo, Timothy; Lee, Chau Hung; Wong, Alvin; Kumar, Naresh; Vellayappan, Balamurugan
Abstract : Abstract: Renal cell carcinoma (RCC) has been traditionally thought to be radioresistant. This retrospective cohort study aims to assess the outcomes of patients with spinal metastases from RCC treated with conventionally-fractionated external beam radiation therapy (cEBRT) in our institution. Patients diagnosed with histologically or radiologically-proven RCC who received palliative cEBRT to spinal metastases, using 3-dimensional conformal technique between 2009 and 2018 were reviewed. Local progression-free survival (PFS), overall survival (OS) and common terminology criteria for adverse events version 4.0-graded toxicity were assessed. Univariable and multivariable Cox proportional hazards regression analyses were performed to evaluate for predictors associated with survivals. Thirty-five eligible patients with forty spinal segments were identified, with a median follow-up of 7 months (range, 0–47). The median equivalent dose in 2 Gy fractions (EQD2 ) was 32.5 Gy 10 (range, 12–39). Thirty-seven percent of patients underwent surgical intervention. At the time of last follow-up, all but 1 patient had died. Seven patients developed local progression, with the median time to local progression of 10.2 months. The median local PFS and OS were 3.3 and 4.8 months. There was no grade 3 or higher toxicity. A higher radiation dose (equivalent dose to 2 Gy fraction <32.5 Gy 10 vs ≥32.5Gy 10 ) (hazard ratio [HR], 0.47; 95% confidence interval [CI], 0.17–3.18; P -value ( P ) = .68) and spinal surgery (HR, 2.35; 95% CI, 0.53–10.29; P = .26) were not significantly associated with local PFS on univariable analysis. Multivariable analysis showed that higher Tokuhashi score (HR, 0.41; 95% CI, 0.19–0.88; P = .02), lower number of spinal segments irradiated (HR, 1.18; 95% CI, 1.01–1.37; P = .04) and use of targeted therapy (HR, 0.41; 95% CI, 0.18–0.96; P = .04) were independent predictors for improved OS. For an unselected group of patients with RCC, there is no significant association between higher radiation dose and improved local control following cEBRT. This may be due to their short survivals. With the use of more effective systemic therapy, including targeted therapy and immunotherapy, survival will likely be prolonged. A tailored-approach is needed to identify patients with good prognosis who may still benefit from aggressive local treatments.